First record of procariama simplex rovereto, 1914 (phorusrhacidae, psilopterinae) in the cerro azul formation (upper miocene) of la pampa province; remarks on its anatomy, palaeogeography and chronological range - Vezzosi, Raúl Ignacio (2012)
New records of Procariama simplex in central and northwestern Argentina are reported. The fossil material includes mandibular bones, cervical vertebrae and several elements of the fore and hindlimbs. After an exhaustive comparison of anatomical characters and morphometric analysis, the fossil specimens are assigned to the psilopterine Procariama simplex. The specimen from La Pampa Province represents the first record of a psilopterine in this central region of Argentina and derives from upper Miocene sediments of the Cerro Azul Formation. Lithological features and biostratigraphical data allow the host bed to be assigned to the Huayquerian faunal stage (late Miocene). The La Pampa record broadens the geographical distribution of Procariama simplex, which was previously restricted to northwestern Argentina.